Amperometric detection of oxygen under humid conditions: The use of a chemically reactive room temperature ionic liquid to 'trap' superoxide ions and ensure a simple one electron reduction - Xiong, L; Barnes, E; Compton, R (Elsevier, 2014)
The amperometric detection of oxygen under moist (humid) conditions via Clark cell type devices using Room Temperature Ionic Liquids (RTILs) as electrochemical solvents can be complicated, because the number of electrons transferred in the electrode reaction varies between one and two as a function of the humidity. The problem is avoided through the use of phosphonium cation based ionic liquids in which the alkyl group of the phosphonium cation has acidic protons which are rapidly abstracted by superoxide ions. Thus the reduction of O2 is to be trapped at the one electron level on the micro-electrode voltammetric timescale, allowing the amperometric detection of oxygen under humid conditions to be quantitatively viable. © 2014 Elsevier B.V.